2001
DOI: 10.1152/jappl.2001.91.6.2546
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of voluntary wheel exercise on apoptosis in splenic lymphocyte subsets of C57BL/6 mice

Abstract: Two-month-old mice were placed in cages with (Ex) or without exercise running wheels with free access to the wheel 24 h/day for 10 mo. An equal amount of food for both groups was provided daily. Ex mice ran an average of 33.67 km/wk initially, and exercise decreased gradually with age. Ex mice had gained an average of 43.5% less body weight at the end of the experiment. Although serum lipid peroxides were not altered by exercise, superoxide dismutase and glutathione peroxidase activities in serum were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
29
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 65 publications
7
29
1
2
Order By: Relevance
“…This finding is consistent with a previous study (Schuler et al 1995). However, with a longer period of voluntary wheel-exercised mice showed a significantly lower weight gain (Russell et al 1987) consequently affecting the immune system (Avula et al 2001). This tendency can be observed between physiological stress and the antibody response.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with a previous study (Schuler et al 1995). However, with a longer period of voluntary wheel-exercised mice showed a significantly lower weight gain (Russell et al 1987) consequently affecting the immune system (Avula et al 2001). This tendency can be observed between physiological stress and the antibody response.…”
Section: Discussionsupporting
confidence: 92%
“…In comparison to the levels measured before the program, the IL-2 levels of the subjects after the 4-week Taekwondo exercise program were found to be elevated. Suzuki et al (24) reported that there was no increase in the secretion of cytokines following endurance training in athletes, and it was demonstrated in another study that IL-2 levels of exercised rats remained unchanged (25). Similarly, Kara et al (6) noted that exercise did not cause any change in the IL-2 levels of individuals performing wrestling as a sport.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, stressful events often precipitate and exacerbate psychiatric disorders such as depression and anxiety (Chorpita and Barlow, 1998;Kendler et al, 1999), and, compared with sedentary rats, several weeks of previous, voluntary access to running wheels results in dramatic alterations in immunological (Dishman et al, 1995;Fleshner, 2000;Avula et al, 2001;Moraska and Fleshner, 2001;Fleshner et al, 2002), neurochemical Dishman et al, 1997b;Soares et al, 1999;Greenwood et al, 2003), and behavioral (Dishman et al, , 1997aSolberg et al, 1999;Moraska and Fleshner, 2001) responses to stress.…”
Section: Introductionmentioning
confidence: 99%